Entirely relaxed lattice-mismatched GaSb/GaAs/Si(001) heterostructure grown via metalorganic chemical vapor deposition. (17th April 2018) - Ha, Minh Thien Huu; Huynh, Sa Hoang; Do, Huy Binh; Nguyen, Tuan Anh; Luc, Quang Ho; Lee, Ching Ting; Chang, Edward Yi
Abstract: A GaSb epilayer is grown on a GaAs/Si(001) epitaxial substrate via metalorganic chemical vapor deposition. High-resolution transmission electron microscopy micrographs and high-resolution X-ray reciprocal space mapping indicate an entirely relaxed interfacial misfit (IMF) array GaSb epilayer. The valence-band offset and conduction-band offset of the Al2 O3 /GaSb/GaAs/Si structure are estimated to be 2.39 and 3.65 eV, respectively. The fabricated Al2 O3 /p-GaSb/GaAs/Si MOS capacitors exhibited good capacitance–voltage characteristics with a small accumulation frequency dispersion of approximately 1.05% per decade. These results imply that the GaSb epilayer grown on the GaAs/Si platform in the IMF mode can be used for future complementary metal–oxide semiconductor applications.